Kingdom of the Netherlands : 2015 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for the Kingdom of the Netherlands-Netherlands. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2016)
This paper presents the overview of the Dutch economy. After a double-dip recession that ended in early 2014, a strengthening but moderate recovery led by exports and investment is underway, although lower production and exports of natural reduced gas reduced growth in the second quarter of 2015, without however interrupting its momentum. Unemployment is falling slowly and inflation is low, but positive. Credit has continued to decline, but demand for credit is gradually rebounding. The Dutch banking system is emerging from its restructuring. The economy now appears set on a gradual path of recovery, and growth is expected to reach 1.9 percent this year and in 2015, supported by an improving domestic demand.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet